Reconciling the different faces of hippocampal theta: The role of theta oscillations in cognitive, emotional and innate behaviors. (February 2018) - Korotkova, Tatiana; Ponomarenko, Alexey; Monaghan, Caitlin K.; Poulter, Steven L.; Cacucci, Francesca; Wills, Tom; Hasselmo, Michael E.; Lever, Colin
Highlights: Theta rhythm is crucial for cognitive functions: memory, spatial and time coding. Theta rhythm is crucial for anxiety-related behaviours. Theta oscillation properties (phase, frequency, amplitude) are linked with behaviors. Parallel emergence of hippocampal theta oscillations and behaviors during development. Abstract: The theta oscillation (5–10 Hz) is a prominent behavior-specific brain rhythm. This review summarizes studies showing the multifaceted role of theta rhythm in cognitive functions, including spatial coding, time coding and memory, exploratory locomotion and anxiety-related behaviors. We describe how activity of hippocampal theta rhythm generators − medial septum, nucleus incertus and entorhinal cortex, links theta with specific behaviors. We review evidence for functions of the theta-rhythmic signaling to subcortical targets, including lateral septum. Further, we describe functional associations of theta oscillation properties − phase, frequency and amplitude – with memory, locomotion and anxiety, and outline how manipulations of these features, using optogenetics or pharmacology, affect associative and innate behaviors. We discuss work linking cognition to the slope of the theta frequency to running speed regression, and emotion-sensitivity (anxiolysis) to its y-intercept. Finally, we describe parallel emergence of theta oscillations, theta-mediated neuronal activity and behaviors during development. This review highlights a complex interplay of neuronal circuits and synchronization features, which enables an adaptive regulation of multiple behaviors by theta-rhythmic signaling.